Challenges of recognition in intimate relationships: a debate with Axel Honneth - Patricia Mattos (Política & Sociedade, 2018)
In dialogue with Axel Honneth I analyse the challenges of recognition in intimate relations in the light of qualitative researches about nowadays romantic love conduced with heterosexual men and women from middle and high middle classes. The researches highlighted the ambiguities which resulted from the growing process of individualization and democratization of gender relations in intimacy. Although recognition in intimate relationships is important for men and women, women manifested very explicitly the deficit of recognition in these relationships – either unrecognition, precarious recognition or misrecognition. I emphasize the forms of female emotional suffering originated from the institutionalization of the sexual field, which splitted sex from emotional involvement, spotting the dilemmas and contradictions of female sexual liberty. If, on the one hand, Honneth’s normative reconstruction of intimate relations can throw light on the tacit moral rules of love interactions and the importance of love for a moral theory of a “good life”, on the other hand it overestimates the potentialities of recognition at the intimate sphere. Additionally, I intend to show the ambivalences of the “new feminism”, as well as the limitations of the contemporary studies on gender and sexuality that emphasize “non-normative” sexualities and the deconstruction of gender binarism, which contradictorily contribute to eclipse gender differences on love and sexuality and, then, hinder the perception of female suffering.